The marvelous thing that came from a spring : the accidental invention of the toy that swept the nation - Ford, Gilbert; Endries, Greg (New York : Atheneum Books for Young Readers, 2016)
Tells the story of how the slinky was invented.
School Library Journal, July 2016
Pub Weekly, July 2016
Booklist, July 2016
Horn Book, April 2017
Bulletin (Center for Children's books), July 2016
Kirkus Review, July 2016
Keywords: Slinky (Toy); James, Richard T., -- 1914-1974.; James, Betty, -- 1918-2008.; Inventors; Slinky (Toy); James, Richard T., -- 1914-1974.; James, Betty, -- 1918-2008.; Inventors -- Biography